Investigation of Adverse Response Expressions to Immune Checkpoint Inhibitor Therapy in PD1-Expressing Non-Small Cell Lung Cancer Patients - Mikaeel, Bran Yousif; Othman, Goran; Salihi, Abbas; Awla, Farhang; Jalil, Omar; Beyaz, Seda; Aslan, Abdullah (Taylor & Francis Inc, 2026)
Lung tumor is the leading cause of tumors in global deaths. The determination of the coefficient reflects that 14% of the HBA1C variation was determined by dose, with the remaining variation reverting to other factors influencing HBA1C. The regression coefficient for dose is 0.158, meaning one unit increase in dose will raise glucose by 0.158 via retention or the current cycle. Determining the coefficient reproduces that 39% of glucose variation is determined by both cycle and dose, with the remaining variation back to other factors touching glucose. The regression coefficient for dose is 0.008, meaning one unit increase in dose will increase HBA1C by 0.008. There is no statistically significant difference in the mean of immunotherapy and chemotherapy of thyroid function tests such as T3, T4, and TSH. Results of subgroup analysis were categorized based on drugs and antibodies used to evaluate immune checkpoint inhibitors, Finally, other tests such as glucose, HBA1C, ACE, and insulin, mean immunotherapy, and chemotherapy for glucose, HBA1C, ACE, and insulin serum were not statistically different. Our results suggest that immune checkpoint inhibitor therapy an important step in the decreasing of lung cancer cells.
Keywords: Immune checkpoint inhibitor; NSCLC; PD1 protein